Bilingual Pedagogy through Translanguaging: A Pathway to Improved Comprehension in EFL Learning - Ali, Areena (Journal of Qualitative Research in Education, 2025)
The present study addressed the efficacy of a translanguaging pedagogy with regard to the English language learners' proficiency and perception in four domains, namely, reading, listening, writing, and speaking. Test-retest difference scores indicated statistically significant improvements in each area, and mean scores changed from 11.69–12.18 to 14.67–15.31 with high t-statistics (20.38–30.9). Qualitative analysis showed four main themes (Cognitive-lists of 50 codes, Interactive-lists of 48 codes, Constructive-lists of 45 codes, Affective-lists of 42 codes), which means that students used L1 strategically to facilitate comprehension, actively took part in cooperative activities, constructed meaning across languages, and felt more confident. These results were supported by the data collected in the surveys: learners gave high ratings to multilingual group work on all the restored variables (understanding M = 4.6, confidence M = 4.4, enjoyment of multilingual group work M = 4.7), and their willingness to recommend the method was 4.5 on average. The consistent positive development in quantitative and qualitative measures would suggest that translanguaging promotes linguistic development, cognitive engagement, social interaction, and affective well-being. Results confirm that using students' first languages in classroom instruction is effective as an equity practice in multilingual classrooms. The research provides empirical data for the translanguaging pedagogical approach as part of skill acquisition and learner agency, with implications for the curriculum design and teacher education in different educational contexts.